Adsorption-Oxidation Mechanism of δ-MnO2 to Remove Methylene Blue. (26th October 2021) - Yan, Ge; Wang, Pu; Li, Yuqian; Qin, Zhangjie; Lan, Shuai; Yan, Yupeng; Zhang, Qin; Cheng, Xiaodi
Abstract : The material, δ -MnO2, has exhibited superior performance on the removal of methylene blue (MB), but the process is significantly impacted by pH, and the impacting mechanism is still unclear. In this study, the effects of pH on the removal mechanism of MB using synthesized δ -MnO2 were investigated by distinguishing the adsorption and oxidation of MB by δ -MnO2 during the removal process in the dark. The results show that the total removal efficiency of MB by δ -MnO2 decreased significantly with an increase in the pH. MB could be removed by δ -MnO2 via an adsorption mechanism and oxidation mechanism, and the proportion of adsorptive removal and oxidative removal was different under different pH conditions. With an increase in the initial pH from 2.00 to 8.05, the redox potential of δ -MnO2 decreased, and its oxidation ability for the removal of MB also gradually decreased. In contrast, the surface negative charges of δ -MnO2 increased with an increase in the pH, and the adsorption ability towards positively charged MB also gradually increased. This indicates that the effects of pH on the removal of MB by δ -MnO2 are primarily dominated by its influence on the oxidation ability of δ -MnO2 . In addition, it is further proved that the pH value has a significant effect on the oxidation and adsorption of MB on δ -MnO2 . Moreover, the significant effects of pH on the oxidation of MB by δ -MnO2 are further demonstrated by observing the changes in Mn 2+ and the UV-Vis spectra of intermediate products during the reaction, as well as the changes in the FTIR and XPS characterizations of δ -MnO2 after the reaction.